2020
DOI: 10.1101/2020.01.04.894915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivocommensal control ofClostridioides difficilevirulence

Abstract: We define multiple mechanisms by which commensals protect against or worsen Clostridioides difficile infection.Using a systems-level approach we show how two species of Clostridia with distinct metabolic capabilities modulate the pathogen's virulence to impact host survival. Gnotobiotic mice colonized with the amino acid fermenter Clostridium bifermentans survived infection, while colonization with the butyrate-producer, Clostridium sardiniense, more rapidly succumbed. Systematic in vivo analyses revealed how … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 107 publications
(82 reference statements)
2
28
0
Order By: Relevance
“…These findings were confirmed with the high levels of spore release in expanded populations of vegetative C. difficile when co-colonized with CSAR (22). Overall, this analysis suggested that the sporulation pathway is an indicator of C. difficile disease, reinforcing the Spo0A-mediated link between sporulation and toxin production recapitulated by the model (Fig.…”
Section: Egrin Uncovers Differentially Active Regulatory Network Dursupporting
confidence: 72%
See 4 more Smart Citations
“…These findings were confirmed with the high levels of spore release in expanded populations of vegetative C. difficile when co-colonized with CSAR (22). Overall, this analysis suggested that the sporulation pathway is an indicator of C. difficile disease, reinforcing the Spo0A-mediated link between sporulation and toxin production recapitulated by the model (Fig.…”
Section: Egrin Uncovers Differentially Active Regulatory Network Dursupporting
confidence: 72%
“…Model predictions also illustrated C. difficile's predicted shift from carbohydrate utilization towards amino acid utilizing pathways in vivo, as shown by the enhanced set of 15 amino acids, including the preferred Stickland donor and acceptor amino acids (leucine and proline) known to support metabolism and growth(43,44,47). Notably, many of these amino acids show high abundance within the gut lumen in gnotobiotic and conventional colonization states that enhance C. difficile's capacity to colonize and expand(22).The Cdiff Web Portal, a resource for the C. difficile communityWe have released a new C. difficile Web Portal (http://networks.systemsbiology.net/cdiff-portal/)to provide a discovery and collaboration gateway for the C. difficile scientific community. The portal aims to accelerate the advancement of the science and understanding of C. difficile biology, gene regulation, and metabolism on its virulence.…”
mentioning
confidence: 89%
See 3 more Smart Citations